Analysis of Supply Chain Management Implementation on MSME Performance - Rahardjo, Budi; Daryono, Daryono; Najmudin, Najmudin (Eastasouth Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in both global and national economies, significantly contributing to job creation, gross domestic product (GDP), and innovation. In Indonesia, MSMEs contribute more than 60% of the GDP and provide over 97% of employment, highlighting the importance of this sector in supporting inclusive and sustainable economic growth. The objective of this study is to analyze the implementation of supply chain management on the performance of MSMEs. This research involves 97 MSMEs, which will be randomly selected as the sample. The data will be analyzed using descriptive statistical analysis and regression analysis. The results of this study show that commitment has a positive influence on supply chain performance in MSMEs, trust has a positive influence on supply chain performance in MSMEs, and information technology has a positive influence on supply chain performance in MSMEs.